Effectiveness of Education and an Antibiotic-Control Program in a Tertiary Care Hospital in Thailand - A. Apisarnthanarak; S. Danchaivijitr; T. Khawcharoenporn; J. Limsrivilai; B. Warachan; T. C. Bailey; V. J. Fraser (My University, 2006)
Background. We conducted a study to evaluate the impact of education and an antibiotic-control program on antibiotic-prescribing practices, antibiotic consumption, antimicrobial resistance, and cost of antibiotics in a tertiary care hospital in Thailand.
Keywords: Tertiary care; Antibiotic Use and Resistance